DIGITALISASI AKSES SISTEM LAYANAN TERPADU UNTUK ANAK STUNTING DI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA DI KOTA MEDAN BERBASIS MOBILE - Silalahi, Hermon Ansfrid Dasarta S; Hutapea, Marlyna Infryanty; Jamaluddin, Jamaluddin (Universitas Methodist Indonesia, 2023)
The Digital Access of stunting services access app is one designed to help build a stunting service center in the resident and family planning terrain service. In addition, to assist ministerial servants in carrying out a filing process. The problem is the computerized process of filing and filing service teams, to prevent stunting service teams from having any difficulty with data-loping, as manuals and archivist data often result in reregisations of the same data that make the data invalid. The goal of the application is to facilitate officers in the process of inquiry, and to assist communities in monitoring stunted child growth. The method used in the study is the waterfall method. The waterfall method is a simple method. It employs a comprehensive and quantifying approach starting at the needs of the system level and heading for the analytical, design, coding, testing or verification and maintenance sequence. The desired result is to facilitate family service in planning information and the ministry and to help build a quick, accurate, stunting service center.